Online Psychological Care and Psychotherapy: Reality, Evidence, and Indicators (The International Journal for Scientific Research, 2023)
The provision of psychological care in its various forms using the Internet has been associated with the emergence of the Internet and the developments seen by various digital media. Multiple justifications exist for using media, including limited resources and difficulty accessing mental health services. The use of remote psychological care has significantly increased during the Covid-19 crisis. The references abound with various discussions and studies on the effectiveness and effects of this type of therapy, the differences from face-to-face therapy, and the qualification requirements of providers. Today, many studies and meta-analyses have examined the effectiveness of internet-based therapy, most likely cognitive-behavioral therapy. The matter still needs more research due to the variety and interrelatedness of the issues raised in this context, especially with reference to the effectiveness of different psychological trends, whether within the same direction or in different directions. It can be concluded that online psychological services are effective, and interventions that combine internet-based elements with organized face-to-face communication have equivalent effects to traditional therapy. Remote psychotherapeutic services should not replace traditional therapy. The provision of psychological services in most Arab countries in its various forms suffers from multiple problems, such as the lack of professional organization and randomness, the absence of philosophy oriented to the humanities and psychology. This review aims to supply a picture of several of the issues raised in the field of psychological services using the Internet and some supporting and opposing points of view without claiming inclusiveness in this presentation.
Keywords: Psychological Care; Psychotherapy; Online Psychotherapy; Face-to-Face Therapy; Cognitive Therapy; Evidence-Based Psychotherapies